English writing motivation on junior high school students: the types and the levels - Arisman, Rizal (Journal of Applied Studies in Language, 2025)
This scientific work intends to explore the sorts and degrees of writing motivation aspects, including enjoyment, self-efficacy, instrumentality, recognition, and effort. The design used is a quantitative approach with the descriptive research method. It involves 166 students at junior high schools in Baubau, Southeast Sulawesi province. An Academic Writing Motivation Questionnaire (AWMQ) is utilized as the research instrument to collect the data. The study discovers that the mean score of the enjoyment aspect is 3.50, the mean score of the self-efficacy aspect is 3.73, the mean score of the instrumentality aspect is 3.98, the mean score of the recognition is 3.97, and the mean score of effort aspect is 3.49. All aspects are categorized at a high level. The instrumentality aspect takes the first place in those results since it possesses the maximum mean score. This result indicates that the students possess strong beliefs that writing serves a practical purpose or is instrumental in achieving specific goals, focusing on the practical benefits of writing. Overall, the average point of writing motivation is 3.70, which is a high level. It means the students are highly motivated toward their writing subject.